Behind the Wheel: Predictors of Driving Exposure in Older Drivers. Issue 6 (1st June 2015) - Coxon, Kristy; Chevalier, Anna; Lo, Serigne; Ivers, Rebecca; Brown, Julie; Keay, Lisa
<x xml:space="preserve">Abstract</x> Objectives To explore and deepen understanding of factors influencing driving exposure for older drivers. Design Cross‐sectional. Setting Baseline data on function and driving exposure from 1 week of driving were evaluated. Participants A convenience sample of 380 drivers aged 75 and older, residing in northwest Sydney, was recruited. Participants were required to be the primary drivers of their own vehicle. Measurements Driver function was evaluated using the DriveSafe and DriveAware clinic‐based assessments to measure visual attention to the driving environment and awareness of driving ability. Demographic information was obtained through interview. An in‐vehicle monitoring device with data logger and GPS receiver, was used to measure driving exposure in 362 of 380 participants' vehicles. Driving exposure outcomes were total distance driven, furthest distance traveled from home, and average trip length. Factors influencing these exposure outcomes were analyzed using generalized linear regression. Results Drivers typically drove 100 km in local and surrounding areas during the week. Function was predictive of all driving exposure outcomes. Drivers with lower levels of function drove fewer kilometers and took shorter trips closer to home. Age, health status, and personal circumstance (e.g., rural residence) also influenced exposure, but sex did not. Conclusion Using objective measures, this study provides evidence that function, age, health status, and personal circumstance influence driving exposure of older drivers. Understanding how older people use driving to preserve their independence is important for exploring safe driving strategies for older people.